2021
DOI: 10.12998/wjcc.v9.i8.1885
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous panniculitis-like T-cell lymphoma invading central nervous system in long-term clinical remission with lenalidomide: A case report

Abstract: BACKGROUND Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) involvement in the central nervous system (CNS) is particularly rare. SPTCL with CNS involvement has an exceedingly poor prognosis, and no optimum therapeutic method has been discovered. To the best of our knowledge, this is the first reported case of SPTCL invading the CNS achieving long-term remission with lenalidomide maintenance therapy. CASE SUMMARY A 63-year-old man diagnosed with SPTCL was admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[ 26 ] Cranial magnetic resonance imaging did not detect any intraparenchymal lesions, and cerebrospinal fluid examination revealed lymphomatous leptomeningeal involvement. Jing Sun et al reported a case of SPTCL after chemotherapy that developed CNS involvement; [ 10 ] a craniotomy biopsy showed CNS T-cell lymphoma, and TCR gene rearrangement showed TCR-β and TCR-γ clonal rearrangement. One SPTCL case developed Epstein-Barr virus-associated CNS B-cell lymphoma after alemtuzumab-CHOP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 26 ] Cranial magnetic resonance imaging did not detect any intraparenchymal lesions, and cerebrospinal fluid examination revealed lymphomatous leptomeningeal involvement. Jing Sun et al reported a case of SPTCL after chemotherapy that developed CNS involvement; [ 10 ] a craniotomy biopsy showed CNS T-cell lymphoma, and TCR gene rearrangement showed TCR-β and TCR-γ clonal rearrangement. One SPTCL case developed Epstein-Barr virus-associated CNS B-cell lymphoma after alemtuzumab-CHOP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the central nervous system (CNS) in the SPTCL is rare. [ 9 , 10 ] We present a case of SPTCL beginning as polycranial neuropathy that presented in a single anatomic site and a single skin lesion that involved the CNS and discuss clinical characteristics, immunohistochemical features, and literature review on SPTCL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation